2014
DOI: 10.1039/c4sc02266a
|View full text |Cite
|
Sign up to set email alerts
|

Two roaming pathways in the photolysis of CH3CHO between 328 and 308 nm

Abstract: We attribute the two product-state distributions previously seen in CH3CHO photodissociation to CH3-roaming and H-roaming, unifying all previous experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 44 publications
4
64
0
Order By: Relevance
“…Among the five transitional modes of each roaming SP, however, few of them are larger than 100 cm -1 in most IRC grids. In order to avoid discontinuity in state-counting results along IRC by the switch between vibration and free-rotor 7 treatments, free-rotor approximation is applied only to the three lowest transitional modes of a roaming SP in the variational RRKM calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Among the five transitional modes of each roaming SP, however, few of them are larger than 100 cm -1 in most IRC grids. In order to avoid discontinuity in state-counting results along IRC by the switch between vibration and free-rotor 7 treatments, free-rotor approximation is applied only to the three lowest transitional modes of a roaming SP in the variational RRKM calculations.…”
Section: Methodsmentioning
confidence: 99%
“…That is, the ionization efficiency is independent of the rovibrational state of the products, which readily compensates for the apparent limitation on the detection sensitivity. 55 A significant problem for measurements of CH3CHO photolysis is formation of clusters in the supersonic expansion, as previously noted by Lee et al 24 Peaks corresponding to (CH3CHO)n clusters up to n = 5 were readily observed in the mass spectrum following VUV ionization. Dissociation of CH3CHO molecules in clusters produces a translationally slow component that dominates the center of the CH3 ion images.…”
Section: Resultsmentioning
confidence: 86%
“…17,22,23 More recent ion imaging experiments, however, have identified translationally slow low-J CO products, with an onset wavelength consistent with the threshold for channel IIb, leading to the suggestion that the radical products CH3CO + H substantially contribute to roaming. 24 Of the two radical product channels, IIa is most important and dominates the long wavelength (λ > 266 nm) photochemistry. 1 The radical products CH3 + HCO can be formed via unimolecular dissociation on S0 following internal conversion or, if sufficient energy is available, dissociation over a barrier on the T1 surface following intersystem crossing.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known problem encountered when working with acetaldehyde expansions is cluster formation. 36,46 Acetaldehyde dimers, trimers, and larger clusters are also observable in the mass spectrum following ionization at 118.2 nm. Ion imaging measurements of CH3 fragments produced by photolysis of the neutral molecule provide a more discriminating diagnostic; under cluster-free conditions, the image at 308 nm appears as a clean, isotropic ring at speeds of ~1700 m s -1 , while photolysis of clusters results in higher ion counts near the center.…”
Section: Resultsmentioning
confidence: 99%